Case report: Rapid onset, ischemic-type gastritis after initiating oral iron supplementation - Koch, Regina M.; Tchernodrinski, Stefan; Principe, Daniel R. (Frontiers in Medicine, 2022)
Oral iron supplements are commonly administered to patients with chronic iron deficiency anemia. This approach is generally well-tolerated, causing only mild adverse effects. Rarely, oral iron supplementation can cause more severe symptoms, one of the most concerning being acute gastritis. This predominantly affects elderly patients and is extremely uncommon in young, otherwise healthy people. Here, we report the case of a 43-year-old woman who presented with upper gastrointestinal (GI) symptoms and iron deficiency anemia and was started on oral iron supplementation following the resolution of her acute symptoms. She soon re-presented with a severe, Helicobacter pylori-negative gastritis with iron deposition on histology. These new onset symptoms resolved rapidly with cessation of iron supplements, consistent with iron pill gastritis. In addition to the limited body of literature describing iron pill gastritis, this case serves as a reminder that any patient receiving oral iron supplementation is at a potential risk for gastritis, particularly in the setting of an ongoing GI pathology. Hence, it is important to provide continued follow-up for patients receiving iron supplementation regardless of age or comorbidity, particularly in the weeks following the start of the treatment.